Starbucks in forbidden city - NETZLEY, Michael A. (Institutional Knowledge at Singapore Management University, 2011)
“Do you have plans to open stores in the Taj Mahal, Versailles, or Buckingham Palace?” China Central Television’s news anchor Rui Chenggang askedJim Donald, Starbucks Chairman and CEO at the June 2006 Yale CEO Leadership Summit. Just over six months later, on 12 January 2007 Rui posted a blog entry protesting against Starbucks’ presence in Beijing’s Forbidden City. Rui stated, “This is not globalization but an erosion of Chinese culture.” Rui’s blog post signalled the start of an avalanche, Starbucks came under attack for operating a café inside China’s Forbidden City. At the time, the Internet presented many Chinese citizens with an unprecedented opportunity to interact and share their opinions. The Internet was still very young in China, in 2007, but it was growing by leaps and bounds. So few could anticipate the response when, in January 2007, Rui, an experienced media personality from CCTV turned this communication channel on Starbucks. The effort to remove the iconic western brand from the centre of the Forbidden City quickly became global news. Initially the story grew only within China’s Internet space, but once translated into English it became global front page news in a matter of days. Starbucks quickly found itself on the receiving end of criticism for inappropriately operating a café in the middle of a cultural and historical centre. The Wall Street Journal, for example, ran an editorial titled “It’s Called Forbidden City for a Reason.”